Clinico-epidemiological profile of snake bite in children in a tertiary care hospital, South India - Dr. Suganthi V.; Dr. Santhi K; Dr. Nandhini S. (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: A high incidence of snake bite envenomation is observed in India, due to rapid urbanization and deforestation. Snake bite is a life-threatening conditionand remains a significant cause for hospital admissions in paediatric age group. Because of their smaller body mass, they have rapid systemic envenomation and high mortality rate. Methods: This is a descriptive type of study about clinical and epidemiological profile of snake bite cases in pediatric age group and also included unknown bites with features of snake bite envenomation. This was done for the period of one year from July 2015 to June 2016. Data about age, sex, bitesite, clinical features, complications, management and outcome were collected and analysed. Results: The study included 54 cases of snake bite victim. Majority were boys (64.8%). The common age group affected was 5-10 years (59%). Lower extremities were the most common site of bites (85%). 42.6% of cases had clinical features within 2 to 6 hours of snake bite. Bite admission interval was 6 hours. Prehospital treatment was employed in 10.3% of patients. In our study, 38.9 % of victimspresented with snake bite of unknown species, 39% known species of snakes and 22.1%were cases of envenomation, where the snake was not visualized. The commonest identified species were viper bite (n=11, 20.4%), followed by rat snake (n=7, 13%) and krait (n=3,5.6%).23(42.6%) cases had dry bite. About 12 (22%) children had local cellulitis; 12 (22%) had combined cellulitis and hemotoxicity; 7 (13%) had neurotoxicity. In our study polyvalent Anti snake venom (ASV) was used in 55.6% of cases and 18.5% of victims developed hypersensitivity reactions to ASV.The case fatality was 11.1% and Krait was the main cause of mortality. Conclusions: Of the children presented with snake bite envenomation, the snake was visualized in majority of cases. Most of them developed clinical features in 2 to 6 hours ofbite. Cellulitis was the commonest presentation and polyvalent ASV was used for treatment. Neurotoxic Krait bite was the commonest cause of mortality.